Dynamic Synergy: The Strategic Interplay Between Entrepreneurial Orientation, Innovation Capability, and Organizational Performance - Kusumawijaya Ida Ketut; Partiwi Dwi Astuti; I Made Hedy Wartana; I Ketut Yudana Adi (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
This study holds particular significance for small and medium-sized enterprises, where limited resources often necessitate the efficient conversion of strategic capabilities into measurable performance outcomes. The proposed conceptual model aims to elucidate the intricate relationships among these variables, providing a comprehensive understanding of the mechanisms that underpin organizational performance in resource-constrained settings. The objective of this research is to explore the direct effects of dynamic capability and entrepreneurial orientation on innovation capability and organizational performance, as well as the mediating role of innovation capability in these relationships. The study employs a cross-sectional survey method, collecting data from 396 SMEs in Bali, Indonesia, using an online questionnaire. The data were analyzed using variance-based structural equation modeling. Results from the analysis reveal that dynamic capability has a strong positive effect on both innovation capability and organizational performance. Entrepreneurial orientation significantly impacts innovation capability, but its direct effect on organizational performance is negligible. However, innovation capability fully mediates the relationship between entrepreneurial orientation and organizational performance. The study also found that mediation analysis of innovation capability on dynamic capability to organizational performance suggest that there is almost no mediating effect.